FOREIGN PRACTICE OF BLOCKCHAIN APPLICATION IN FINANCIAL REGULATION OF LAND USE AND DIRECTIONS OF ITS IMPLEMENTATION IN UKRAINE (INNOVATIVE ECONOMY, 2026)
Kurbetskyi S.М. FOREIGN PRACTICE OF BLOCKCHAIN APPLICATION IN FINANCIAL REGULATION OF LAND USE AND DIRECTIONS OF ITS IMPLEMENTATION IN UKRAINEPurpose. The aim of the article is to analyse foreign practice of blockchain application in financial regulation of land use and outlining directions of its implementation in Ukraine.Research methodology. Monitoring, comparison, analysis and synthesis methods were used in the research process. The research methodology was based on identifying differences between the processes of blockchainization of land use in Georgia, Serbia and Estonia through the prism of their technological and institutional level of development. The use of the monitoring method made it possible to collect information about the features of blockchain application in financial regulation of land use in Georgia, Serbia and Estonia, the analysis helped in the study of individual components of the considered practices, and the synthesis became the basis for their unification to propose directions of implementation in Ukraine.Findings. The essence of the digital transformation of land use in post-socialist Georgia, Serbia and Estonia is revealed. The approaches of the governments of these states to blockchainization of land use are explained and the prerequisites and features of these processes are mentioned. The advantages of integrating blockchain technologies into the land registries of Georgia, Serbia and Estonia and their impact on the practices of financial regulation of land use are identified.Originality. The need to modernize the domestic land registry through the use of distributed registry (blockchain) technologies is substantiated. The directions for implementing blockchain in the financial regulation of land use in Ukraine are established, which involve the work of the expert community, legislators and groups of landowners on legislative, social and technological modernization in accordance with the norms of the EU legal system. For the first time, ways to achieve the implementation of blockchain in the financial regulation of land use in Ukraine are identified. Practical value. The formulated ways to achieve blockchainization of the financial regulation of domestic land use can be useful for blockchain innovators and specialists in the field of working with the land registry during preparation for its technological modernization and further use of the land information system of Ukraine.Key words: land use, blockchain, financial regulation, digitalization, transformation, land registry.
Keywords: land use; blockchain; financial regulation; digitalization; transformation; land registry